An Overview and Critique of US Immigration and Asylum Policies in the Trump Era. (September 2019) - Schmidt, Paul Wickham
Executive Summary: This article provides an overview and critique of US immigration and asylum policies from the perspective of the author's 46 years as a public servant. The article offers a taxonomy of the US immigration system by positing different categories of membership: full members of the "club" (US citizens), associate members (lawful permanent residents, refugees, and "asylees"), friends (nonimmigrants and holders of temporary status), and persons outside the club (the undocumented). It describes the legal framework that applies to these distinct populations and recent developments in federal law and policy that relate to them. It also identifies a series of cross-cutting issues that affect these populations, including immigrant detention, immigration court backlogs, state and local immigration policies, and constitutional rights that extend to noncitizens. It ends with a series of recommendations for reform of the US asylum system, and a short conclusion.